Formation and catalytic activity of partially oxidized Pd nanoparticles - Libuda, Jörg; et al. (SPRINGER/PLENUM PUBLISHERS, 2007)
Combining multi molecular beam ( MB) experiments and in-situ time- resolved infrared reflection absorption spectroscopy ( TRIRAS), we have studied the formation and catalytic activity of Pd oxide species on a well-defined Fe3O4 supported Pd model catalyst. It was found that for oxidation temperatures up to 450 K oxygen predominantly chemisorbs on metallic Pd whereas at 500 K and above (-10)(-6) mbar effective oxygen pressure) large amounts of Pd oxide are formed. These Pd oxide species preferentially form a thin layer at the particle/ support interface. Their formation and reduction is fully reversible. As a consequence, the Pd interface oxide layer acts as an oxygen reservoir providing oxygen for catalytic surface reactions. In addition to the Pd interface oxide, the formation of surface oxides was also observed for temperatures above 500 K. The extent of surface oxide formation critically depends on the oxidation temperature resulting in partially oxidized Pd particles between 500 and 600 K. It is shown that the catalytic activity of the model catalyst for CO oxidation decreases signifcantly with increasing surface oxide coverage independent of the composition of the reactants. We address this deactivation of the catalyst to the weak CO adsorption on Pd surface oxides, leading to a very low reaction probability.
Keywords: model catalysts; surface reaction kinetics; molecular beams; surface oxidation; palladium; iron oxide; CO oxidation